The time course of adaptations in thermoneutral maximal oxygen consumption following heat acclimation - Waldron, M.; Jeffries, O.; Tallent, J.; Patterson, S.; Nevola, V. (European Journal of Applied Physiology, 2019)
Purpose: This study investigated the effects of a 10-day heat acclimation (HA) programme on the time course of changes in thermoneutral maximal oxygen uptake (VO2max) during and up to 10 days post-HA. Methods: Twenty-two male cyclists were assigned to a HA or control (Con) training group following baseline ramp tests of thermoneutral VO2max. Ten days of fixed-intensity (50% baseline VO2max) indoor cycling was performed in either ~ 38.0 °C (HA) or ~ 20 °C (Con). VO2max was re-tested on HA days 5, 10 and post-HA days 1, 2, 3, 4, 5 and 10. Results: VO2max initially declined across time in both groups during training (P < 0.05), before increasing in the post-HA period in both groups (P < 0.05). However, VO2max was higher than control by post-HA day 4 in the HA group (P = 0.046). Conclusions: The non-linear time course of VO2max adaptation suggests that post-testing should be performed 96-h post-training to identify the maximal change for most individuals. In preparation for training or testing, athletes can augment their aerobic power in thermoneutral environments by performing 10 days HA, but the full effects will manifest at varying stages of the post-HA period.